Advanced Machine Learning Technologies and Applications First International Conference, AMLTA 2012, Cairo, Egypt, December 8-10, 2012, Proceedings - Hassanien, Aboul Ella; Salem, Abdel-Badeeh M.; Ramadan, Rabie; Kim, Tai-hoon (Communications in Computer and Information Science, 2012)
This book constitutes the refereed proceedings of the First International Conference on Advanced Machine Learning Technologies and Applications, AMLTA 2012, held in Cairo, Egypt, in December 2012. The 58 full papers presented  were carefully reviewed and selected from  99 intial  submissions. The papers are organized in topical sections on rough sets and applications, machine learning in pattern recognition and image processing, machine learning in multimedia computing, bioinformatics and cheminformatics, data classification and clustering, cloud computing and recommender systems.